2009
DOI: 10.4314/jmbr.v4i1.10669
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral and parafunctional habits in Nigerian patients suffering temporomandibular joint pain and dysfunction

Abstract: Pain and dysfunction of the temporo-mandibular joint (TMJ) still pose a therapeutic dilemma to the oral and maxillofacial surgeon. Epidemiological data on the disorder in Nigerians appear not to be available, as only few studies are recorded.1 Studies from North America revealed a prevalence rate of 12.1% amongst adults, 2 although some authors have claimed that pain, clicking and locking have been experienced by approximately 20% of the general population. Pain in the joint and muscles is often distressing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
9
2
2
Order By: Relevance
“…These results are similar to those described by other studies in the literature, where the authors reported 58% for anxiety and 23% for depression ( 25 ), 15% moderate depression and 13% severe depression ( 19 ), 21% depression in the group of patients with joint pain, 26% in the group with myofascial pain and 25% in the group with myofascial and joint pain ( 26 ) and 19% of patients with severe depression ( 4 ). There are some differences in the results of this study when compared to the 40% for moderate and severe depression ( 18 ) or even the 25% for anxiety ( 27 ). These differences should not be credited only to methodological differences, but they may also be explained by differences in cultural, social and economic factors, education, the health of the researched population, and the fact that the questionnaires used to determine the rate of anxiety and depression in the studies mentioned are based on values of societies that are different from the individuals in this study ( 18 , 27 ).…”
Section: Discussioncontrasting
confidence: 63%
“…These results are similar to those described by other studies in the literature, where the authors reported 58% for anxiety and 23% for depression ( 25 ), 15% moderate depression and 13% severe depression ( 19 ), 21% depression in the group of patients with joint pain, 26% in the group with myofascial pain and 25% in the group with myofascial and joint pain ( 26 ) and 19% of patients with severe depression ( 4 ). There are some differences in the results of this study when compared to the 40% for moderate and severe depression ( 18 ) or even the 25% for anxiety ( 27 ). These differences should not be credited only to methodological differences, but they may also be explained by differences in cultural, social and economic factors, education, the health of the researched population, and the fact that the questionnaires used to determine the rate of anxiety and depression in the studies mentioned are based on values of societies that are different from the individuals in this study ( 18 , 27 ).…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, about one forth of patients with temporo-mandibular joint pain and dysfunction have nail biting habit [7]. …”
Section: Resultsmentioning
confidence: 99%
“…Saheeb and Otakpor reported that mental disorders (e.g. generalized anxiety disorder and dysthymic disorder) were found in 37.5% of the patients who complained of pain and dysfunction of temporomandibular joints 17 . According to the report by Korszun et al ., 28% of their patients were diagnosed as having major depressive disorder and 25% with minor depressive disorder; 22% of their patients had depressive symptoms, although they did not satisfy the criteria for diagnosis of depressive disorders 18 .…”
Section: Discussionmentioning
confidence: 98%